2020
DOI: 10.31577/ekoncas.2020.10.03
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Bankruptcy of Slovak Companies Using Neural Networks with SMOTE

Abstract: Although the bankruptcy prediction models can be a stabilizing element on both macro and microeconomic levels, they are rather a domain of academic research than an instrument, widely applied in a business practice. It is especially true if the models are reflecting the conditions of countries of their origin, rather than countries of their intended uses. Besides, few of the models contain inherent flaws, including the absence of a methodical approach addressing this problem of the severely imbalanced represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Moreover, these studies, together with other studies, have shown that the financial situation of companies can be predicted based on financial ratios. These originally applied classification methods were recently replaced by the studies of Antunes et al (2017), Divsalar et al (2012), Geng et al (2015), Kovacova and Kliestik (2017), Mendes et al (2010), Xie et al (2011), andTumpach et al (2020) that applied data mining techniques like decision trees (DTs), LR, support vector machines (SVMs), neural networks (NNs), Bayesian networks, gene expression programming, or random forests (RFs). Xie et al (2011) showed that MDA and SVM classification methods achieve more than 80% accuracy.…”
Section: Classification Methods Of Bankruptcy Predictionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, these studies, together with other studies, have shown that the financial situation of companies can be predicted based on financial ratios. These originally applied classification methods were recently replaced by the studies of Antunes et al (2017), Divsalar et al (2012), Geng et al (2015), Kovacova and Kliestik (2017), Mendes et al (2010), Xie et al (2011), andTumpach et al (2020) that applied data mining techniques like decision trees (DTs), LR, support vector machines (SVMs), neural networks (NNs), Bayesian networks, gene expression programming, or random forests (RFs). Xie et al (2011) showed that MDA and SVM classification methods achieve more than 80% accuracy.…”
Section: Classification Methods Of Bankruptcy Predictionmentioning
confidence: 99%
“…Therefore, the authors recommended further verifying the proposed methodology's effectiveness on a larger data sample. Tumpach et al (2020) developed an NN model and worked with a highly imbalanced data sample that reflected a real-life dataset of companies with an occurrence of bankrupting companies of 0.32%.…”
Section: Classification Methods Of Bankruptcy Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Musa [46] proposed a complex prediction model based on discriminatory analysis, logistic regression, and decision trees. On the other hand, Tumpach et al [47] use oversampling with the synthetic minority oversampling technique (SMOTE). In the Czech Republic, Neumaier and Neumaierova [48] generated the prediction model on the principle of MDA.…”
Section: Literature Reviewmentioning
confidence: 99%